REPOSISI PERAN SUTRADARA DALAM MANAJEMEN PRODUKSI PROGRAM TELEVISI DI INDONESIA - Widodo, Agus; Moebin, Amrullah Ali; Cahyono, M Rudi (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
This article aims to discuss how the role of the director shifts in the management process of television program production. In recent years the director's role has been considered to have shifted regarding his duties to manage the course of production. The driving factor is in the form of technology that shifts market needs that are increasingly diverse. Therefore it is important to look back at how they carry out their new tasks, the positive impacts and challenges they experience. Using a case study by Robert K Yin which is focused on MNCTV media. The results of the study show that repositioning of the director (program director) has a significant role as a form of adaptation to the content and creative process of a production program. However, it is necessary to align creative and managerial roles. One of them is the development of education as an increase in competence.